Faktor-Faktor Yang Mempengaruhi Perilaku Pemeriksaan Payudara Sendiri (SADARI) Pada Mahasiswi Non Kesehatan UIN Antasari Banjarmasin - Septi Anggraeni; Eka Handayani (HB PRESS, 2019)
Cancer is one of the leading causes of death worldwide. In Indonesia, more than 80% of breast cancer cases are found at an advanced stage, where treatment is difficult. Therefore, it is necessary to take preventative measures with early diagnosis through regular routine checks, one of which is by Self Breast Examination (BSE). This study was conducted to determine the factors that influence the behavior of BSE in non-medical students UIN Antasari Banjarmasin with a cross sectional study design with a sample of 50 female students. Data processing analysis includes univariate analysis, bivariate analysis and multivariate analysis with multiple logistic regression statistical tests. Descriptively obtained results that only 13 people (26%) did BSE, respondents' knowledge 38% in good category, attitude towards BSE 84% positive, source of information about BSE 22% in many categories, perceptions of family support 28% supporting and perception about peer support 24% supports. To determine the factors that influence BSE, multiple logistic regression statistical tests were performed which showed the results that there was a joint influence between knowledge, exposure to information sources, perceptions of family and peer support on BSE behavior with a large influence of 35.6 %. To improve the behavior of BSE, it is necessary to increase knowledge, information sources, family and peer support together. Keywords : Knowledge, attitude, Family support, Information Exposure, BSE